Generation, characterization, and environmental implications of solid waste and its management in the Everest region (Nepal Journal of Environmental Science, 2021)
Managing solid waste is becoming a rather challenging task in remote areas, including the Mt. Everest region in Nepal, due to its cold climate, complex topography, and extreme environmental factors. Using published and unpublished literature and personal communications to key informants, this paper analyzes the situation of solid waste management in the Everest region as it relates to increasing tourism and possible environmental implications in the region. The study revealed that combined efforts from people of all levels associated with the mountain region would create a circular waste management system. The paper also reports the existing practices and planned activities for the essential process such as source segregation of waste, collection, use of material recovery facility, and recycling which could lead to sustainable solid waste management in the Everest region and beyond with similar context.